1983
DOI: 10.2527/jas1983.5651186x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization Failure and Embryonic Mortality in Parous and Nonparous Beef Cattle1

Abstract: One hundred and two nonparous females, 18 to 24 mo old, and 55 parous or multiparous beef females, 3 to 12 yr old, were mated naturally (d 0) and slaughtered on d 2 to 5, 6 to 8 or 14 to 16 of gestation. Each reproductive tract was flushed with phosphate-buffered saline, and the flushings were searched for an oocyte or embryo. Parous females had a higher (P less than .05) fertilization rate than nonparous females. In nonparous females, reproductive failure was attributed equally to fertilization failure and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 0 publications
6
40
1
1
Order By: Relevance
“…This is in agreement with a report that low-fertility cows that had failed to produce a calf in either 1 or 2 previous seasons did not demonstrate a failure in ovulation (Warnick and Hansen, 2010). Because conception rates are relatively high in beef cows (Maurer and Chenault, 1983), this would suggest a greater rate of embryonic loss in repeat breeder cows, as has been reported previously (Maurer and Echternkamp, 1985;Warnick and Hansen, 2010). Thus, oocyte quality may be the connection between decreased follicle numbers and subfertility in heifers and cows.…”
Section: Discussionsupporting
confidence: 81%
“…This is in agreement with a report that low-fertility cows that had failed to produce a calf in either 1 or 2 previous seasons did not demonstrate a failure in ovulation (Warnick and Hansen, 2010). Because conception rates are relatively high in beef cows (Maurer and Chenault, 1983), this would suggest a greater rate of embryonic loss in repeat breeder cows, as has been reported previously (Maurer and Echternkamp, 1985;Warnick and Hansen, 2010). Thus, oocyte quality may be the connection between decreased follicle numbers and subfertility in heifers and cows.…”
Section: Discussionsupporting
confidence: 81%
“…Beef producers replace 12% to 15% of the cow herd annually, but a lower pregnancy rate for heifers necessitates retention of additional heifers (Maurer and Chenault, 1983). Management of replacement heifers from weaning to breeding is critical to their lifetime productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical pregnancy was about for 40% for both repeat breeders and controls. Maurer and Chennault [12] reported that 67% of embryonic death in cattle occurred within 8 days after fertilization. We attemped ET to reduce the early embryonic losses and within 6 days after ET (equivalent to 13 days after estrus) detected the presence of EPF.…”
Section: Discussionmentioning
confidence: 99%